Determinants of Indonesian Processed Tuna Export Performance in the Japanese Market: An Empirical Analysis of IJEPA Tariff Preferences and MHLW Sanitary Regulations - I Putu Dio Hariza Putra; Ketut Vini Elfarosa; Eldian Rinaldi (Journal of Social Work and Science Education, 2027)
Indonesia possesses abundant tuna resources and benefits from preferential tariff facilities under the Indonesia–Japan Economic Partnership Agreement (IJEPA). However, the export volume of Indonesian processed tuna to Japan continues to fluctuate despite tariff reductions and increasingly stringent sanitary regulations imposed by Japan’s Ministry of Health, Labour and Welfare (MHLW). This study aims to examine the effects of IJEPA tariff preferences and MHLW sanitary regulations on the export volume of Indonesian processed tuna exported to Japan. A quantitative explanatory approach was employed using monthly secondary time-series data from January 2020 to December 2024, comprising 60 observations. The data were analyzed using multiple linear regression following classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, followed by partial, simultaneous, and coefficient of determination analyses. The findings reveal that neither IJEPA tariff preferences nor MHLW sanitary regulations significantly affect export volume, either individually or simultaneously. The novelty of this study lies in integrating tariff preferences and sanitary regulations within a single empirical model interpreted through the Blue Economy perspective. Practically, the findings recommend improving logistics efficiency, food safety compliance, and fisheries governance. This study contributes to international trade literature by demonstrating that structural factors beyond trade policy instruments play a more decisive role in sustaining Indonesia’s processed tuna exports to the Japanese market.